Terapia baseada na mentalização: aspectos teóricos, epistemológicos e metodológicos - BRUNO MARQUES IBANES (2024)
This research investigated Mentalization-Based Therapy (MBT), analyzing its theoretical foundations, clinical practices, and epistemological implications. Developed in the 1990s based on the theories of Peter Fonagy and collaborators, MBT integrated concepts from various disciplines, such as psychoanalysis and attachment theory, to treat psychological disorders, with a focus on Borderline Personality Disorder. The reviewed articles highlighted the historical trajectory of MBT, the central concept of mentalization, and its theoretical bases, in addition to specific technical practices. Despite the advancements, the research presented limitations, such as the dependence on previous empirical studies, the simplification of complex theoretical constructs, and the scarcity of longitudinal studies. Additionally, there was a lack of clarity about evidence-based practices and the positioning of attachment theory as a developmental theory. The applicability of MBT in non-clinical contexts was still incipient, not allowing it to be considered a complete ontology. Recognizing these limitations is crucial to promoting a better theoretical and practical integration of MBT. Future studies should focus on developing longitudinal research, exploring the effectiveness of MBT in different contexts and populations, and deepening the integration of attachment theory with psychoanalysis to meet the contemporary demands of psychotherapy.